Interculturality scale, beyond the qualitative perspective: a measurable tool at Abya Yala territory - Henríquez-Coronel, María Angélica (2025)
Ecuador, as part of Abya Yala, has institutionalized the principle of interculturality, promoting its analysis primarily through qualitative approaches. However, there remains a limited availability of quantitative instruments capable of measuring this dimension, which motivated the development of a scale adapted to the regional context. The objective of this research was to psychometrically validate an instrument designed to assess perceptions and conceptions of interculturality among university students in Ecuador. A psychometric analysis was conducted on a 27-item Likert-scale instrument, applied to education students from two Ecuadorian universities. The study evaluated reliability using Cronbach’s alpha coefficient, construct validity through exploratory factor analysis, and discriminant capacity using the Student’s t-test for independent samples. The results showed high reliability (α = 0.925) and adequate construct validity, revealing a five-component structure that accounts for 68.17% of the total variance. The findings highlight the instrument’s usefulness for measuring interculturality in the region and across various fields of knowledge. Nonetheless, some implementation challenges were identified, revealing conceptual and cultural barriers that represent key areas for future pedagogical intervention.